Role of School and Out of School Education in Forming Ecological Culture of Senior Pupils - Oleh Fasolia (Pedagogical Discourse, 2016)
The article deals with the role of school and out of school education in forming ecological culture of senior pupils. The terms «ecological education», «ecological upbringing», «ecological culture» have been revealed. Special role in forming ecological culture of senior pupils is played by the senior school with its ecological profile, optional courses «Bases of Ecological Knowledge», school ecological societies, etc. Out of school educational establishments of ecological direction function effectively. To them belong regional ecological-naturalistic centers, ecological stations, studious. Today support of young talents and gifted children is very important for the forming creative and scientific elite in the sphere of environment protection, stimulating creative self-perfection of children and pupils by means of conducting different ecological actions: olympiads, competitions, festivals and other forms of out of class activity. Organization of ecological education of schoolchildren is considered to be successful, when ecological erudition of a pupil is manifested in everyday behavior, in specific acts and work, in attitude to the environment – that is in active ecological activity of a personality.Key words: ecological education, ecological upbringing, ecological culture, school (formal) education, out of school (informal) education.